# If #f(x) = x^2# and #g(x) = x + 2#, what is #(f@g)(x)#?

To view another example, click the link provided below.

By signing up, you agree to our Terms of Service and Privacy Policy

(f@g)(x) = f(g(x)) = f(x + 2) = (x + 2)^2. Therefore, (f@g)(x) = x^2 + 4x + 4.

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- How do you find vertical, horizontal and oblique asymptotes for # f(x) = (x^2 - 9) / (x - 4)#?
- How do you find the asymptotes for #g(x) = (4x^2+11) /( x^2+8x−9)#?
- How do you find the Vertical, Horizontal, and Oblique Asymptote given #f(x) = (2x - 3)/( x^2 - 1)#?
- How do you find the end behavior of #f(x) = -2(x-1)(x+3)^3#?
- How do you find the inverse of the function: #f(x)= 6+ sqrt(x+7)#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7